A Chinese familial growth hormone deficiency with a deletion of 7.1 kb of DNA. Issue 3 (March 1990) - He, Y A; Chen, S S; Wang, Y X; Lin, X Y; Wang, D F
Abstract : Using restriction endonuclease analysis and a human growth hormone cDNA probe, we have found a Chinese family with a human growth hormone gene deletion. Two affected sibs are homozygous for a deletion of approximately 7.1 kb of DNA, which contains the normal human growth hormone gene. The patients' parents and grandmothers are heterozygous for the deleted gene. Their grandfathers are normal and homozygous for the hGH-N gene. All of them have normal stature.